Study of the Position of the Court Decision as a requirement to fulfil the condition of "Important Event" as in the Recording of the Application for Gender Reassignment - Putri Purbasari; Vanka Aurellia (Jurnal Perkotaan, 2024)
Gender change is the choice and right of every individual. In Indonesia, there are no specific regulations regarding gender change. However, the rules regarding gender changes are closely related to Article 56, paragraph (1) of the Civil Administration Law (UU Adminduk) and its explanation. Article 56, paragraph (1) of the Population Administration Law states that the Civil Registration Officer records other essential events at the resident's request after obtaining a court decision with permanent legal force. Transgender or transsexual individuals have the same rights as other members of society or different genders, both men and women. Indonesian law recognizes that every human being is a legal subject. Article 1, paragraph (1) of the Civil Code (KUH Perdata) states that enjoying civil rights does not depend on political rights. This article aims to show that the conditions set by the state do not determine a person's position as a legal subject. Humans are recognized as legal subjects from birth until death. However, in reality, transgender or transsexual groups often receive unfair treatment from society and even the government. There have been many cases where a transsexual who applied for a gender change after undergoing gender reassignment surgery was rejected. Gender change or gender reassignment surgery is every human's right and must be legally protected. Every person with sexual orientation and gender identity has the right to enjoy all their human rights. Everyone is born free and equal in rights and dignity. Everyone also has the right to recognition before the law, and those with different sexual orientations and gender identities must also receive total legal capacity and equal rights.